PENDIDIK DALAM PERSPEKTIF AL-QUR`AN - Nasharuddin Yusuf (An-Nida', 2011)
The study of educators the perspective of al-Qur’an extremely unique and exciting, it has its own urgenitas identity that can assemble with noble character educators. There is no holy book, and no is the theory that any one can deliver the ideal educator, except holy book al-Qur’an. Al-qur’an gives the role of humans as Abdullah and khalifatullah fi al-ard, in order to bothroles were implemented, people need education. Education can be implemented through the educator’s role as a cleric, al-mudararis, al-muallim, al-murshid, almurabbiy, al-cleric, nad syarih (pensyarah). Terms of educators who use islam is not only synonym ous terms, but has the identity of the ideal educator, he has significance and must be updated in order to bequeath tamaddun Islam, which form a civil society. The nature of educators that can bequeath a civilization that values akhlaqi,convey its mission to rahmatan li al-‘alamin. This paper, it would seem that a true educator by qur’ani, for educator who qur’ani there was a professional educator who can shape participants intellegence students into the realm of intellectual, moral, emotional, social and spritual